Serious and Opportunistic Infections in Elderly Patients With Inflammatory Bowel Disease - Lin, Elissa (Gastroenterol Hepatol (N Y), 2019)
Inflammatory bowel disease (IBD) is often treated with biologics and immunomodulators, which can place elderly IBD patients at risk for serious and opportunistic infections. This article provides an updated account of research on therapies in IBD that are associated with an increased infection risk. Relevant serious and opportunistic infections in the elderly population are discussed along with methods for prevention and treatment. The incidence of infection increases with age and the degree of immunosuppression. Emphasis should be placed on performing vaccinations at the time of IBD diagnosis. Additionally, patients receiving immunosuppressive therapy should avoid live vaccines. Physicians should have a greater awareness of the increased risk of infection in elderly adults and the need for screening for infection prior to initiation of immunosuppressive IBD therapies.